Predictors of Parenting Behavior and Parenting Satisfaction among Parents that Transited in Parenting during the War in Croatia - Kuterovac-Jagodić, Gordana (Array, 2008)
Studies have documented a relationship between different parental stressors and parenting behavior, but effects of war on parenting behavior has not been studied often. This study examined relationship between subjective war stress, parental mental health indices (depression and aggressive and hostile behavior), perceived social support and self-reported parenting behaviors and parenting satisfaction. The sample consisted of 812 pairs of mothers and fathers from 10 Croatian cities and towns differently affected by the war 1991-1995. The mean age of mothers was 39 and fathers 42 years at the time of data collection, i.e. 25 and 28 at the beginning of the war. The average number of children per family was two, and their age at the time of the study ranged from 10 to 15 years. There were 54.7% daughters and all the children were born during the war in Croatia. Parents Separate hierarchical regression analyses were performed for maternal and paternal positive and negative parenting and parenting satisfaction as dependent variables. In each regression parental demographic variables were entered first (age and education), followed by self perceived negative effects of war on relationship with others, on life values and on life circumstances were entered in the second step, depressive and aggressive and hostile behavior entered in the third step, and social support entered in the last step. The results indicate significant association of self perceived negative effects of war, parental mental health and social support with their parenting behavior and satisfaction. These associations suggest that war and negative mental health indices may have deleterious effects on parental behavior and parenting satisfaction, while self perceived social support seems to have beneficial effect on positive parental behaviors and parental satisfaction but not on negative parental behaviors.